Pemberdayaan Masyarakat Melalui Penerapan Metode Ovitrap dan Budidaya Tanaman Pengusir Nyamuk Sebagai Upaya Penanganan Demam Berdarah Dengue (DBD) di Kelurahan Tanjung Mas Kota Semarang - Fahmi, Fatimatul; Pantiawati, Ika; Anggraini, Reny Diva; Nuraeni, Puspa Ayu; Abiyasa, Maulana Tomy (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2024)
This service activity aims to increase the knowledge and skills of community members in handling dengue hemorrhagic fever through the ovitrap method and cultivating mosquito-repellent plants. The method of implementing this service uses empowerment with socialization and practical activities. This service establishes a partnership with Dian Nuswantoro University (UDINUS) in the form of Assisted Village Partners, Semarang City Health Service, and Bandarharjo Community Health Center providing support in the form of mentoring and speakers, and the Forest Plant Certification and Seedling Center (BSPTH) providing support in the form of 100 eucalyptus plant seeds. The evaluation instrument for this activity uses a pre-test and post-test. This service data analysis technique uses descriptive analysis. The results of this service show that community members have the knowledge and skills to deal with dengue hemorrhagic fever through the ovitrap method and cultivating mosquito-repellent plants in Tanjung Mas Village. This is proven by residents participating in the process of making Ovitrap tools and planting mosquito-repellent plants. There was a change in community knowledge from before the counseling was carried out to after the counseling was carried out (the score before the counseling was 35, and the score after the counseling was 50).